Tingkat pemahaman finansial literasi terhadap gaya hidup mahasiswa - Adinda, Adinda; Ifrah, Marsyanda; Kurnianingsih, Heny Triastuti (Proceeding of National Conference on Accounting & Finance, 2024)
To ascertain the Islamic University of North Sumatera pupils' comprehension of financial literacy. The growing prevalence of impulsive purchases and consumer behavior that goes beyond acceptable bounds begs the important issue, "Do students, particularly those enrolled in accounting study programs, understand financial literacy?" Thus, a survey was designed with 26 respondents in mind. According to the survey results, there are fewer students at the Islamic University of North Sumatra who lack financial literacy. In fact, several respondents said they have never used financial reports in their day-to-day activities.